Long‐term patterns in the establishment, expansion and decline of invading macrozoobenthic species in the brackish and marine waters of Southwest Netherlands. (8th July 2013) - Hummel, Herman; Wijnhoven, Sander
Abstract: The fluctuations in densities or biomass of a number of invading and native polychaete and mollusc species in the Southwest Netherlands were compared over a period of 20 years. For recent invaders a lag phase of 7–10 years occurred after their first appearance, followed by an exponential increase in abundance or biomass for 2–3 years. High numbers and biomass then continued for about 5 years, followed by a strong decline. The total sequence from introduction to decline lasted about 15 years. The densities or biomass of invaders appearing decades or even centuries ago in the Delta area have fluctuated in a similar manner to those of native species, indicating that the densities or biomass of invading species after a 15‐year period of strong changes become governed largely by the same environmental factors as native species. The conclusion may be that after some decades, invading species can become part of a balanced co‐existence with the native species, and that this may yield a net gain in the overall diversity.